Impact of market expectations on the U.S. interest rate lift-off in ASEAN-5 financial system - Ooi, Teik-Khim (Springer, 2021)
During 2015–2016, the market has lowered its expectations on the pace and magnitude of U.S. interest rate lift-off, which should have reduced capital outflow and supported the ASEAN-5 financial markets. Yet, the ASEAN-5 financial markets have recorded mixed fortunes, possibly due to spikes in global risk (proxied by CBOE VIX index). Against the contrasting background of higher global risk and gradual interest rate lift-off, this paper investigates the impact of market expectations on U.S. interest rate on the ASEAN-5 financial markets. This paper concludes that both global risk and market expectations on interest rate lift-off affect the ASEAN-5 financial markets, whereby the negative effect of higher global risk dominates the positive effect of market expectations of gradual interest rate lift-off in the ASEAN-5 currencies and equity markets. However, it is the reverse in the ASEAN-5 sovereign bonds as the positive impact of market expectations of more gradual interest rate lift-off dominates the negative effect of higher global risk. © 2020, Springer Japan KK, part of Springer Nature.